2020
DOI: 10.1021/acsomega.0c02403
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanosheets Containing Uniformly Dispersed PdII Ions at an Aqueous/Aqueous Interface: Development of a Highly Active Nanosheet Catalyst for Mizoroki–Heck Reaction

Abstract: A method was developed to synthesize a nanosheet at the interface of an aqueous layer of Pd II ions and an aqueous layer of hydrophilic polymer bearing a metal coordination unit (HPMC). The nanosheet was synthesized through generation of an interface by the addition of an aqueous solution of Pd II ions with a low specific gravity (1.03 g/cm 3 ) to a dispersed aqueous solution of HPMC with a high specific gravity (1.50 g/cm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The TOF values were considered to compare the catalytic performance. Among them, Ma et al 62 and Nagai et al 63 reported high catalytic performance for the Heck reaction using IB and MA to produce MCIN reaching a TOF of 16,000 and 13,889 h −1 , respectively, which is 2.5‐fold higher than our proposed catalytic system. These high catalytic activities are attributed to the nature of the polymer component in the catalyst system, which corresponds to the soluble macromolecules stabilizing the Pd II ‐based active site.…”
Section: Resultsmentioning
confidence: 64%
“…The TOF values were considered to compare the catalytic performance. Among them, Ma et al 62 and Nagai et al 63 reported high catalytic performance for the Heck reaction using IB and MA to produce MCIN reaching a TOF of 16,000 and 13,889 h −1 , respectively, which is 2.5‐fold higher than our proposed catalytic system. These high catalytic activities are attributed to the nature of the polymer component in the catalyst system, which corresponds to the soluble macromolecules stabilizing the Pd II ‐based active site.…”
Section: Resultsmentioning
confidence: 64%
“…On the basis of this mechanism for the formation of gels with different morphologies, the gelation of HPMC-8 with Au III provided nanofiber containing uniformly dispersed Au nanoparticles by a facile method, i.e., dropwise addition of a dispersed aqueous solution of HPMC-8 to an aqueous solution of Au III ions [24]. In contrast, the faster gelation of HPMC-8 with Pd II provided nanosheets containing uniformly dispersed Pd II ions via gelation at the interface between the aqueous phases of Pd II and HPMC-8 [25]. Nanosheets can be synthesized with a bottom-up method [19][20][21][22][23], which occurs at the interface between an organic polydentate ligand and an aqueous layer containing metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a bottom-up synthesis broadens the diversity and utility of nanosheets. We previously investigated the gelation behavior of a hydrophilic polymer bearing metal-coordination units (denoted as HPMC) with metal ions (Pd II or Au III ) upon addition of a dispersed aqueous solution of HPMC-8 to an aqueous solution of metal ions [24,25]. HPMC-8 consists of thiocarbonyl groups (8 mol%) for metal coordination and hydroxyl groups (92%) for hydrophilicity (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to develop an approach that simultaneously improves the surface area of MnO 2 and eliminates the mentioned limitations. The liquid-liquid interface synthesis is one of the effective strategies for nanomaterials, nanosheets, and polymers synthesis due to the particular physical properties favoring particle self-organization [11][12][13]. Furthermore, a large variety of metal oxides has been prepared via deposition at liquid-liquid interfaces with the well-ordered particle arrays [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%